Renewing universities of the third age: challenges and visions for the future - Formosa, Marvin Formosa (RECERCA. Revista de Pensament i Anàlisi, 2012)
The University of the Third Age [UTA] has developed into a global success story. Whether holding a ‘top-down’ administrative arrangement or embodying a culture of selfhelp, there can be no doubt as to the triumph of UTAs in meeting the educational, social, and psychological needs of older persons. However, on the basis of fieldwork conducted at the UTA in Malta a cautionary note must be warranted. UTAs may also function as yet another example of glorified occupational therapy that is both conservative and oppressive. At the same time, UTA models seem to be running the risk of becoming obsolete as societies embark on a ‘late-modern’ model of the life course in which the sequential division between learning, work and retirement is becoming increasingly blurred. This article calls for the UTA movement to go through a cultural revolution to remain relevant to contemporary ageing lifestyles. Six key directions are forwarded: embracing a trans formational rationale, ensuring that access overcomes class, gender and ethnic biases, guaranteeing that teaching and learning strategies are skilfully suited to older persons, making greater use of eLearning techniques, extending its activities to frail and physically dependent older people especially those in residential/nursing homes, and organising activities that promote intergenerational learning. Las universidades para mayores se han convertido en una iniciativa de gran éxito mundial. Ya sea por su organización administrativa «de arriba abajo» o por encarnar una cultura de autoayuda, de lo que no cabe duda es que han conseguido cubrir las necesidades educativas, sociales y psicológicas de las personas mayores. No obstante, a raíz del trabajo de campo llevado a cabo por la Universidad de la Tercera Edad en Malta, hay que poner una nota de cautela. Estas universidades podrían quedarse como un ejemplo más de terapia ocupacional glorificada con un carácter tanto conservador como opresor. Al mismo tiempo, los modelos de las universidades para mayores parecen correr el riesgo de quedarse obsoletos a medida que las sociedades adoptan un modelo «tardomoderno» del curso de vida en el que se va desdibujando la división secuencial entre aprendizaje, trabajo y jubilación. Este artículo reclama que el movimiento de universidades para mayores experimente una revolución cultural que tenga sentido para los estilos de vida contemporáneos de las personas mayores. Así, se proponen seis indicaciones: adoptar una lógica transformacional; garantizar un acceso sin prejuicios de clase, género o raza; garantizar que las estrategias de docencia y aprendizaje sean técnicamente apropiadas para las personas mayores; incrementar el uso de las técnicas de aprendizaje a distancia; extender sus actividades a personas mayores con salud delicada o físicamente depen dientes y en particular a aquellas que están en residencias o clínicas; y, por último, organizar actividades que promuevan el aprendizaje intergeneracional.